(untitled) (Revista Brasileira de Contabilidade e Gestão, 2022)
With the complications caused by the worsening of the pandemic caused by the coronavirus, which started in 2020, where several sectors had their activities interrupted or even paralyzed, several employees had their working hours reduced or interrupted, forcing them to find alternatives to reposition themselves in the workplace. labor market. In this context, the term workability can be mentioned, which, according to Maltby (2011), aims to improve the quality of work, encouraging better mental and bodily health, relating the work environment with the personal environment. The main objective of this study was to identify and analyze factors that influence human development and workers’ workability. After multivariate analysis, using the SPSS software, it was possible to identify two main factors that correspond to the presented study. The first factor identifies characteristics linked to the personal development of workers, while the second factor refers to questions about suitability and job satisfaction as determining factors in the professional development of workers. The importance of satisfaction as a criterion for professional improvement was also observed. This research also contributes to a better interpretation of the relationship between employer and employee, in addition to enabling different perspectives on the appreciation of technical and interpersonal skills such as improvement in the work process, professional appreciation and capture of new technical and emotional skills to better perform the work. and generate value through these.